KEBIJAKAN PEMERINTAH INDIA DALAM MENGATASI MASALAH‘DOWRY DEATHS’ - Jusmalia Oktaviani; Siti Muti'ah Setiawati (Universitas Jenderal Ahmad Yani, 2017)
This study explains about the policy of the Indian governmentin addressing the problem of ‘dowry deaths’ in India. Dowrydeaths itself is a term for a murder or violence against wives inwhich performed by the husband or the husband's familybecause of the inability of the wife to meet the demand of payingthe dowry. The impact of the tradition of giving dowry is not onlythe death of the wives, but also the impact on the discriminationover the women and selective abortion of female fetuses. Thenumber of victims of dowry death reached more than 8000deaths per year.The phenomenon of dowry deaths required the Indiangovernment to intervene to resolve the issue. Indian governmenthave managed to make some policies, it covers the application ofthe rules of prohibiting dowry in the marriage that began with theDowry Prohibition Act of 1961, that punish the offender of dowrydeath with the threat of no less than seven years in prison; andalso, some policies to provide financial incentives to daughter, toprohibit the sex-selective abortion to female fetuses. In addition,the Indian central government's policy is also supported by theinitiative of the state government to initiate several relatedpolicies such as banning ultrasound technology, forbiddingabortion, as well as providing incentives to girls, and variousother policies. Although the government has been implementingvarious policies, but the weakness of law enforcement caused bythe strong patriarchal culture in society is one reason why thesepolicies are less effective in preventing loss of life because of'dowry deaths'.